Sadd al-Zari'ah and Extra-Judicial Divorce: A Critical Discourse Analysis of MUI Fatwa and KHI Legal Frameworks - Ahmad Agum Manoppo; Firman Muhammad Arif; Muhammad Tahmid Nur (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The objective of this research is to examine the "comparison of the law on divorce outside the court from the perspective of Sadd al-zari'ah in the MUI fatwa and KHI." This study employs library research using a descriptive analysis method, which involves collecting, organizing, classifying, and interpreting data. The findings of this study reveal that the law on divorce outside the court, according to the MUI fatwa of 2012, states that such a divorce is valid if it meets certain conditions, including the presence of a shar'i reason, the wife's iddah period starting from the pronouncement of divorce, and a subsequent report to the court. In contrast, according to the KHI, as stipulated in Articles 115 and 117, divorce is only valid if conducted in the presence of a religious court hearing, making divorces outside the court invalid. The analysis of Sadd al-zari'ah suggests that the KHI's perspective is more relevant in preventing harm, such as ambiguity in marital status, administrative difficulties in marriage registration, and neglect of the rights of wives and children. Therefore, the MUI fatwa of 2012 requires reformulation to better align with contemporary contexts and minimize the negative impacts of divorces occurring outside the court.